The Correlation Between Learning Facility, Learning Time and Parental Guidance at Home to The Students’ English Learning Achievement - Fatmawaty, Riryn; Hafidz, Moh; Isnani, Zakiya; Maria, Theofanny (Tarbiyah : Jurnal Ilmiah Kependidikan, 2022)
The research purpose is to know the correlation between learning facility, learning time and parents’ guidance at home to the students’ English learning achievement. The research uses a correlation method with the subject of the study is 118 participants of the students of English Education Program. All of the key words are parents’ participation to support the students’ success in learning. However , the students need motivation not only from the school teacher but also from the parents at home. Due to students spend most of the time at home with the parents.  The data are collected by using documentation and questionnaire. The researcher uses SPSS 25 to calculate and answer each variable’s hypothesis. Then the researcher uses F statistic and multi correlation to answer the hypothesis of all variables. Based on the research result, F change 0.001 < 0.05, It means the hypothesis is accepted and there is significance correlation of learning facility learning time and parental guidance towards students’ learning achievement. In conclusion, it can be inferred that every unit increase in learning indicators such as; learning facility, learning time and also parental support are accompanied by a unit change in student achievement in English.